Aligned Electrospun PLLA/Graphene Microfibers with Nanotopographical Surface Modulate the Mitochondrial Responses of Vascular Smooth Muscle Cells. Issue 13 (29th May 2021) - Li, Min; Deng, Wenshuai; Zhang, Jun; Zheng, Weiping; Yu, Tao; Zhou, Qihui
Abstract: Although electrospun polymer fibers with unique (bio)physicochemical features have been demonstrated to regulate cellular phenotype, their specific effect on organelles has not been examined closely. Herein, this work investigates the impact of aligned electrospun poly(L‐lactic acid) (PLLA)/graphene (Gr) microfibers with the nanoporous surface on the mitochondrial responses of human aorta smooth muscle cells. Highly aligned PLLA/Gr microfibers with an average fiber diameter of ≈1.3 µm are prepared via a novel stable jet electrospinning strategy. Nanoporous topography is formed onto individual fiber surfaces using highly volatile solvent dichloromethane and suitable ambient humidity. Further, it is found that the addition of Gr in PLLA fibers significantly facilitates the formation of mitochondrial reactive oxygen species (mROS) and adenosine triphosphate (ATP) as well as mitochondrial autophagy and division by upregulating the protein expression of microtubule‐associated protein light chain 3, mitochondrial fission 1 protein, and dynamin‐related protein 1. In contrast, the introduction of the nanoporous structure greatly inhibits the generation of mROS and ATP as well as mitochondrial autophagy and division. The work thus indicates that the incorporation of nanotopography and Gr in/on the PLLA fibers can offer additional physicochemical stimuli to regulate the mitochondrial responses of cells. Abstract : Highly aligned electrospun poly(L‐lactic acid)/graphene microfibers with nanoporous surface are developed via a novel stable jet electrospinning. For the first time, the effects of graphene and nanotopography on the mitochondrial metabolites are demonstrated. The designed fibers can offer additional physicochemical cues to modulate the mitochondrial responses of cells.